COMPARATIVE ANALYSIS OF e-ADVERTISEMENT BETWEEN TOKOPEDIA AND SHOPEE - Mawuntu, Keren A.; Pangemanan, Sifrid S.; Tielung, Maria V.J. (FEB Universitas Sam Ratulangi Manado, 2020)
The emergence of internet technology has created online advertising as the significant approach of commercial communication all over the world. Advertising has been defined as any paid form of non-personal communication of ideas and information about products in the media with the objective of creating brand image. The development of e-commerce in Indonesia has mushroomed based on MMX Multi-Platform on 2017 showed top 10 e-Commerce in Indonesia. The aim of this study is to analyze the difference of e-Advertisement between 2 big e-Commerce in Indonesia which are Tokopedia and Shopee. This research is a quantitative research and uses independent sample t-test. The sample size of this research is 100 customers of both e-Commerce. The results showed that there are 3 variables that there is no significant difference in e-Advertisement between Tokopedia and Shopee, and the rest were has a significant differences, by referring to the results of observations of online advertising between Tokopedia and Shopee, it was found that there is no difference, so the two big e-commerce companies should maximize their online marketing by determining the right segmentation. so that the direction of marketing is more measurable.Â Keywords: e-Advertisement, independent sample t-test, website design effectiveness, website security and privacy effectiveness, of information quality, brand recognition, demography.